STRATEGI PEMASARAN DI MIM AL-AKBAR PANDEYAN - Al Lutfu Subakri (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2022)
This study aims to describe the marketing strategy carried out at MIM Al-Akbar Pandeyan.  This study uses a qualitative method with a descriptive qualitative design.  The subjects of this study were the deputy principal, TU teachers, and the PPDB MIM Al-Akbar Pandeyan implementation committee.  Data collection techniques used are interviews, observations, and documentation in schools, this research uses source triangulation.  The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions.  The results of this study indicate that the marketing strategy carried out by MIM Al-Akbar Pandeyan is using brochures, MMT, social media, and pick-up the ball, while the marketing strategy carried out during COVID 19 is more directed to MMT and social media due to physical distancing.  which resulted in not being able to carry out a pick-up-ball marketing strategy as well as temporary closures at schools and online learning in the 2020/2021 Academic Year.  The marketing strategy in the 2021/2022 Academic Year was carried out again before the pandemic.